Mediating role of waqf literacy on the impact of knowledge, experience, and capacity building on the performance of waqf institutions in East Java, Indonesia - Siswahyudianto, Siswahyudianto; Al Idrus, Salim; Munir, Misbahul; Ningsih, Sri Wahyuni (Journal of Islamic Economics Lariba, 2026)
IntroductionWaqf institutions in Indonesia hold substantial potential to contribute to socio-economic development, yet their performance remains constrained by suboptimal asset utilization and limited managerial capacity. In East Java, many waqf assets are not managed productively, highlighting the need to strengthen human capital and institutional effectiveness. In this context, knowledge, experience, and coaching are critical factors that may influence institutional performance, while waqf literacy is increasingly recognized as an important capability for improving governance and decision-making.ObjectivesThis study aims to examine the influence of knowledge, experience, and coaching on the performance of waqf institutions in East Java. It also investigates the mediating role of waqf literacy in explaining how these human capital factors contribute to institutional performance.MethodThe study employs a quantitative explanatory design using survey data collected from 194 respondents within the Indonesian Waqf Board in East Java. The sample was selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling to test both direct and indirect relationships among knowledge, experience, coaching, waqf literacy, and institutional performance.ResultsThe findings indicate that knowledge and coaching have significant positive effects on institutional performance, while experience does not show a direct effect. Knowledge, experience, and coaching significantly improve waqf literacy, which in turn positively affects performance. Waqf literacy fully mediates the relationship between experience and performance and partially mediates the relationship between coaching and performance, but it does not mediate the effect of knowledge.ImplicationsThe results suggest that waqf institutions should prioritize knowledge enhancement, structured training, and literacy development to improve performance. Emphasis should be placed on competency-based human resource strategies and continuous capacity building to ensure effective and sustainable waqf management.Originality/NoveltyThis study contributes to the literature by developing an integrated model that highlights the selective mediating role of waqf literacy in linking human capital factors to institutional performance, offering new insights into waqf management in Indonesia.